Unlegitimate grief of transsexual people in the gender adjustment process (Research, Society and Development, 2023)
On the margins of non-legitimized grief, where society often silences singular pains, this research will address the phenomenon of non-legitimized grief in transgender people during and after the gender adjustment process. Mourning carries with it the representation of feelings of sadness resulting from someone's death, linked to pain and anguish. Furthermore, gender identity and transsexuality are addressed, highlighting the importance of depathologization and social acceptance. The research seeks to understand the complexities of such grief and its respective implications due to non-recognition, aiming to improve psychological support, increase public awareness and promote the social inclusion of transgender people. The focus group methodology was used to carry out this research, where, based on participants' reports, it was possible to collect information about the researched topic.